Teacher and EFL Primary School Students’ Perspectives on the Shadowing Technique for Pronunciation Instruction - Wati, Shafrida; Idami, Zahratul (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
This study elaborates the perspectives of teachers and primary school students learning English as a Foreign Language (EFL) regarding the application of the shadowing technique for pronunciation. Scholars have acknowledged shadowing as an effective technique for improving learners' pronunciation, where pupils replicate speech as carefully and promptly as possible following a speaker. This qualitative study was carried out at MIN 2 Langsa throughout the academic year of 2022-2023. Subject of the research was an English teacher and 30 fifth-grade pupils selected purposively. Data were gathered through semi-structured interviews with an EFL teacher and focus group discussions with the primary school students, followed by classroom observations to provide a deeper comprehension of the actual use of the method. Thematic analysis was employed to identify key patterns and themes in participants' responses. Results revealed that teacher considered the technique effective for enhancing students' speech accuracy, rhythm, and intonation. It offers students an immediate opportunity to correct their pronunciation and actively involves them in learning English, particularly in terms of pronunciation. The learners primarily viewed shadowing activity as an enjoyable exercise, where they practiced English chorally. This technique fosters students' confidence in the English classroom by alleviating individual pressure, while all participants learn and practice English together. Thus, it can be a powerful tool for enhancing young learners’ pronunciation in an engaging way. English teachers might employ the technique as an alternative strategy to engage young learners in foreign language acquisition, particularly in pronunciation.